Academic libraries as community resource partners for entrepreneurs. Issue 3 (10th August 2015) - Griffis, Patrick
Abstract : Purpose: – The purpose of this paper is to provide examples and best practices of an academic library's strategy of collaborating with community agencies in assisting community entrepreneurs. Design/methodology/approach: – This conceptual paper reflects on the evolution of a new service role for an academic library in providing outreach to community entrepreneurs and is limited to the best practices and lessons learned of one academic library. Findings: – This conceptual paper reflects on an academic library's outreach strategy for assisting community entrepreneurs; collaboration with community agencies is featured as a best practice with examples and lessons learned. Originality/value: – A recent national study of academic business librarians' outreach to entrepreneurs has established collaboration with community agencies as an effective service strategy. This conceptual paper reflects on the use of this strategy in a specific academic library's outreach efforts to community entrepreneurs.